A docência no curso de licenciatura em física da UFPA: história e gênero - MATOS, Maria da Conceição Gemaque de (Universidade Federal do Pará, 2012)
This study aimed to analyze the inclusion of females in the teaching of the Degree in Physics from UFPA, in the period 1970-2005, aiming to identify the difficulties and barriers experienced by teachers in the academic context, influenced by social models and cultural riches offered by the genre they belong to. The proposed period, the Brazilian education has undergone educational reform perspectives and different profiles, leading to an emerging need to expand the faculty in various segments of higher education. The research problem was framed in three questions, namely: 1) As the authors devoted to addressing gender studies in their productions historiographical trajectory of upward mobility of females and their fight for higher education? 2) how the proposals for teacher training inspired by the Brazilian educational legislation influenced the inclusion of females in the teaching of the Degree in Physics from UFPA, between 1970 to 2005? 3) What are the main barriers to teaching women brought along the training and work with a degree in physics in this educational institution? The research was set up in long-term perspective of the historiography seeking to understand the intertwined gender and training established in the webs of higher education in UFPA. Working with bibliographic and documentary sources are added to a discourse analysis of teachers through semi-structured interview, highlighted the cultural and social settings experienced by Brazilian women to reach higher education and space science, won through much struggle and determination, since the acquisition knowledge to them was not considered necessary, instituting labels dualized in the teaching profession, passing the building aspect of discrimination in females at their practice. Educational reforms did not elucidate the gender category. The degree studied here remains with the hegemonic presence of male teachers.